2018
DOI: 10.1016/j.powtec.2017.12.035
|View full text |Cite
|
Sign up to set email alerts
|

The process for making low density LAS surfactant detergent agglomerates using microwave heating

Abstract: The internal structure of detergent surfactant agglomerates is modified using electromagnetic heating to produce a lower bulk density final product. The agglomerates are heated in a 1.8 KW microwave waveguide heating applicator operating at license-free ISM frequency band of 2450 MHz. The density of the agglomerates reduces significantly when exposed to high power electromagnetic fields. The effect of number of process variables such as input power initial moisture content over bulk density of detergent partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Hinton investigated a new detergent and numerous detergent recipes in 2002 (Ranji et al 2019). In 2018, Sandhu et al revealed that electromagnetic heating altered the internal structure of detergent surfactant agglomerates, resulting in a product with a lower bulk density (Sandhu et al 2018).…”
Section: Introduction 11 History Of Detergentsmentioning
confidence: 99%
“…Hinton investigated a new detergent and numerous detergent recipes in 2002 (Ranji et al 2019). In 2018, Sandhu et al revealed that electromagnetic heating altered the internal structure of detergent surfactant agglomerates, resulting in a product with a lower bulk density (Sandhu et al 2018).…”
Section: Introduction 11 History Of Detergentsmentioning
confidence: 99%
“…Zamora and Alvarez investigated about these environmental impacts in surface sediments at the south end of the Southern California Bight (Figure 1). 6 Among a variety of these components, they choose LABs to study detergents environmental impacts at the mentioned area because other pollutants whose chemical behavior is similar to that of LABs may also have the same fate. Their main purpose of this study was to investigate the extent of the impact of municipal water discharges on southern SCB sediments.…”
Section: Introductionmentioning
confidence: 99%